Evaluasi Pelaksanaan Program Magang Guru Produktif Bersertifikat Industri Pada SMK Pusat Keunggulan Di Kota Denpasar - Sudiarta, I.G.; Sunu, I.G.K.A.; Widiana, I.W. (Pascasarjana Universitas Pendidikan Ganesha, 2023)
This study aims to describe the effectiveness of the implementation of an industry-certified productive teacher apprenticeship program at the Center for Excellence Vocational School in Denpasar City in terms of variables: context, input, process, and product. Then evaluate jointly in terms of context, input, process, and product, as well as the constraints encountered and the solutions to the implementation of an industry-certified productive teacher apprenticeship program at the Center for Excellence Vocational School in Denpasar City. The subjects in this study were 56 productive teachers who had implemented an industry-certified teacher apprenticeship program and were selected based on a purposive sampling technique. This research is evaluation research with a quantitative approach using the CIPP model (context, input, process, and product). Data were collected using questionnaires, documentation, and interviews and were analyzed descriptively and quantitatively. Data analysis was performed by converting the raw score into a Z score (z-score) followed by a T score and then converted into the Glickman quadrant. The results of the study show the effectiveness of the implementation of the industrial-certified productive teacher apprenticeship program from the context of obtaining effective results (+), the effectiveness of the implementation of the industrial-certified productive teacher apprenticeship program in terms of the input obtained effective results (+), the effectiveness of the implementation of the industrial-certified productive teacher apprenticeship program in terms of process obtained less effective results (-), the effectiveness of the implementation of the industrial-certified productive teacher apprenticeship program in terms of the product obtained effective results (+). Overall, the evaluation of the context, input, process, and product variables in the implementation of the industrial-certified productive teacher apprenticeship program at a vocational center of excellence in Denpasar city is classified as effective (+ + - +).